Development Of A Low Cost And Low Loss Single Phase Grid Tie Inverter For Photovoltaic Application - Tan , Kheng Kwang (2012)

(untitled)
This thesis present a single phase H-bridge grid tie inverter developed for photovoltaic application. The objectives for this design are simplicity, efficiency, stability and compact size. Base on these objectives, the H-bridge inverter topology is chosen to be the design. Besides that, LC passive harmonic filter is used to remove the harmonic contains and a grid frequency transformer is used to step up the output voltage of the inverter to the grid voltage. Moreover, hybrid switching technique is chosen to be the switching topology of this designed inverter.